Intestinal Dendritic Cells in Health and Gut Inflammation - Stagg, Andrew J. (Frontiers in Immunology, 2018)
Dendritic cells (DCs) mediate tolerance to food antigens, limit reactivity to the gut microbiota and are required for optimal response to intestinal pathogens. Intestinal DCs are heterogeneous but collectively generate both regulatory and effector T cell responses. The balance of outcomes is determined by the activity of functionally distinct DC subsets and their modulation by environmental cues. DCs constantly sample luminal content to monitor for pathogens; the significance of the various pathways by which this occurs is incompletely understood. Intestinal DC have distinctive properties shaped by local host, dietary and microbial signals. These properties include the ability to produce all-trans retinoic acid (RA) and imprint gut tropism on T cells they activate. In the steady-state, subsets of intestinal DC are potent generators of inducible Treg, aided by their ability to activate TGFand produce RA. However, responses induced by steady-state intestinal DCs are not exclusively regulatory in nature; effector T cells with specificity for commensal bacterial can be found in the healthy mucosa and these can be locally controlled to prevent inflammation. The ability of intestinal DCs to enhance effector responses in infection or sustain inflammation in disease is likely to involve both modulation of the local DC population and recruitment of additional populations. Immune pathways in the pathogenesis of inflammatory bowel disease can be mapped to DCs and in inflamed intestinal tissue, DCs show increased expression of microbial recognition machinery, activation, and production of key immunological mediators. Intestinal DCs may be targeted for disease therapy or to improve vaccine responses.